2019
DOI: 10.1002/fsn3.920
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal assessment of aluminum contents in foodstuffs and aluminum intake of residents in Tianjin metropolis

Abstract: Aim In this report, we retrieved and analyzed the data of aluminum contents in foodstuffs over a 6‐year span between 2010 and 2015 and assessed the risk of dietary aluminum exposure in residents of Tianjin metropolis. Methods A multistage random clustering method was used to survey Tianjin residents between 2010 and 2015. Samples were mainly purchased from breakfast vendors, farmers’ markets, and supermarkets in Tianjin between 2009 and 2015. A total of 1,814 persons ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Furthermore, a study showed that, during product preparation, parameters such as exposure processing time, temperature, and the amount of alum used influence the retention and therefore the total concentration of aluminum in jellyfish tissues [25]. According to another study conducted by Ma et al [30], a very low concentration of aluminum in fish products was observed, while on the contrary, high values of this metal were found in jellyfish caught in the same area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a study showed that, during product preparation, parameters such as exposure processing time, temperature, and the amount of alum used influence the retention and therefore the total concentration of aluminum in jellyfish tissues [25]. According to another study conducted by Ma et al [30], a very low concentration of aluminum in fish products was observed, while on the contrary, high values of this metal were found in jellyfish caught in the same area.…”
Section: Discussionmentioning
confidence: 99%
“…Another limit is the exiguous quantity of studies (one) about microbiological risk [17]. As concerns the chemical risk, we have to consider that the study conducted by Ma et al [30] refers to a Chinese city, Tianjin, where the policies governing the amount of aluminum food additives have not been respected and, consequently, it cannot be affirmed whether or not the results of this work are generalizable. Yang et al [32] in their study report other three limitations.…”
Section: Limitation Of the Studymentioning
confidence: 97%
See 1 more Smart Citation
“…Three other studies [ 71 , 72 , 73 ] that examined Al content in the jellyfish often eaten by people were carried out in three cities in China. Ma et al [ 71 ] studied residents in the Tianjin metropolis for 6 years from 2010 to 2015, and determined the risk of being exposed to dietary Al. During their research, 21.14% of the food samples contained more Al residue than that recommended (100 mg/kg).…”
Section: Potential Risks Related To Eating Jellyfishmentioning
confidence: 99%
“…Aluminum (Al) is among the most enriched metals in our biosphere. Despite its extensive use in daily life (adjuvanted vaccins [29] and other pharmaceuticals [30], food additives [31,32], cosmetics…), Al has unknown biological function [33].…”
Section: Introductionmentioning
confidence: 99%